THE EFFECT OF BRAND TRUST, BRAND IDENTIFICATION AND BRAND COMMITMENT ON BRAND LOYALTY OF SHOES SPORTS - Avianita Rachmawati; Sutrisno Sutrisno; Saiful Saiful (Jurnal Ekonomi, 2023)
Business growth is currently growing rapidly, where competition is very tight, making many sports shoe companies continue to improve quality according to current trends. 2020 was a tough year for companies due to the covid 19 pandemic. So many companies are competing to create the advantages of their respective company brands so that they can always compete with existing brands. So this research was conducted with the aim of knowing the effect of brand trust, brand identification, brand commitment and brand loyalty on sports shoe brands. The method used is secondary data, where the data collected is 315 respondents. In this study researchers used a sample size of 10:1